The Late Permian in the Muarádzi Sub-basin, Moatize-Minjova Basin, Mozambique: multidisciplinary palaeoenvironmental characterization [Resumo] - Lopes, Gilda (2022)
ABSTRACT: A study involving lithofacies, palynofacies, and palynological analysis is presented for the Muarádzi Sub-basin. This sub-basin is part of the Moatize-Minjova Basin (MMB), a crucial Karoo aged coalfield in Mozambique previously situated in the southern-central part of Gondwana.